2007
DOI: 10.1038/sj.emboj.7601911
|View full text |Cite
|
Sign up to set email alerts
|

ERK activation causes epilepsy by stimulating NMDA receptor activity

Abstract: The ERK MAPK signalling pathway is a highly conserved kinase cascade linking transmembrane receptors to downstream effector mechanisms. To investigate the function of ERK in neurons, a constitutively active form of MEK1 (caMEK1) was conditionally expressed in the murine brain, which resulted in ERK activation and caused spontaneous epileptic seizures. ERK activation stimulated phosphorylation of eukaryotic translation initiation factor 4E (eIF4E) and augmented NMDA receptor 2B (NR2B) protein levels. Pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
106
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 53 publications
6
106
0
2
Order By: Relevance
“…In fact, in an in vivo study, phospho-ERK levels were shown to increase after a behavioural seizure detection (Houser et al, 2008). Inhibiting ERK signaling might be useful for seizure control (Nateri et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in an in vivo study, phospho-ERK levels were shown to increase after a behavioural seizure detection (Houser et al, 2008). Inhibiting ERK signaling might be useful for seizure control (Nateri et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that the depleted GluN2B protein levels observed in the present study are a consequence of increased internalisation due to decreased phosphorylation of GluN2B Y1472 . Nateri et al [21] suggests that MEK1 overexpression in mice leads to elevated hippocampal GluN2B protein levels through increased ERK phosphorylation and subsequent activation of eIF4E. In that study, GluN2B levels were not associated with those of phosphorylated GluN2B Y1472 .…”
Section: Discussionmentioning
confidence: 62%
“…Although androgens are reported to stimulate synaptogenesis [40], our results do not support an engagement of eIF4E in the synaptic fraction at least not within the time frame tested in the present investigation. Looking up-stream of NMDAR regulation, ephrinB2 is a protein that stimulates the phosphorylation of GluN2B at Y1472 through Fyn kinase [21,22]. Moreover, it is also known to regulate synaptic plasticity [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because NMDA receptor targets of conantokins have been strongly implicated in epileptogenesis (34,42,51), the pharmacological activity of the stapled conG analogs was speculated to result from antagonism of these receptor targets. Compared with the native peptide, stapled conG analogs possessed similar efficacy in suppressing seizure activities.…”
Section: Discussionmentioning
confidence: 99%